2006
DOI: 10.1152/ajpendo.00451.2005
|View full text |Cite
|
Sign up to set email alerts
|

DHT and testosterone, but not DHEA or E2, differentially modulate IGF-I, IGFBP-2, and IGFBP-3 in human prostatic stromal cells

Abstract: Prostate cancer is one of the four most common cancers in the United States, affecting one of six men. Increased serum levels of androgens and IGF-I are associated with an augmented risk of prostate cancer. Dihydrotestosterone (DHT) and testosterone (T) stimulate prostate cancer cell growth, development, and function, whereas the effects of DHT and T in prostate stromal cells, and of dehydroepiandrosterone (DHEA) in prostate cancer or stromal cells, are uncertain. We investigated the actions of DHT, T, DHEA, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
49
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 54 publications
7
49
0
Order By: Relevance
“…However, the proliferative response of LAPC-4 to the presence of stromal cells, regardless of the hormone treatment, was significant with 2-3 fold increases in cell numbers within 3 days, similar to prior results published in normal or cancer prostate cells [27]. Multiple stromal cell secreted growth factors may contribute to this proliferative effect, including IGF-1, EGF, HGF, KGF, FGF [8,[28][29][30][31], as well as nvolvement of extracellular matrix proteins [25].…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…However, the proliferative response of LAPC-4 to the presence of stromal cells, regardless of the hormone treatment, was significant with 2-3 fold increases in cell numbers within 3 days, similar to prior results published in normal or cancer prostate cells [27]. Multiple stromal cell secreted growth factors may contribute to this proliferative effect, including IGF-1, EGF, HGF, KGF, FGF [8,[28][29][30][31], as well as nvolvement of extracellular matrix proteins [25].…”
Section: Discussionsupporting
confidence: 87%
“…The prostatic primary stromal cells used in this study (6S) were previously found to increase expression of IGF-1 and IGFBP2 and decrease IGFBP3 in response to treatment with DHT but not with DHEA [8]. The current study focuses on DHEA effects on LAPC-4 cells which, like normal (non cancerous) prostate luminal cells, contain a wild type AR [10].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations